2016
DOI: 10.1093/mnras/stw1676
|View full text |Cite
|
Sign up to set email alerts
|

Common envelope events with low-mass giants: understanding the transition to the slow spiral-in

Abstract: We present a three-dimensional (3D) study of common envelope events (CEEs) to provide a foundation for future one-dimensional (1D) methods to model the self-regulated phase of a CEE. The considered CEEs with a low-mass red giant end with one of three different outcomes -merger, slow spiral-in, or prompt formation of a binary. To understand which physical processes determine different outcomes, and to evaluate how well 1D simulations model the self-regulated phase of a CEE, we introduce tools that map our 3D mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 38 publications
0
61
0
1
Order By: Relevance
“…Initial attempts to model CE events were limited to 1-dimensional studies, such as those reported by Taam et al (1978), Meyer & Meyer-Hofmeister (1979), and Delgado (1980). Using such 1-d studies, three phases have been identified in the evolution of CE simulations (Podsiadlowski 2001;Ivanova 2002): first the loss of co-rotation phase, in which the initial embedding of the binary within the envelope occurs. This phase may occur over a long time-scale (depending on the nature of the onset of CE evolution), with the expected initial co-rotation of the system leading to low rates of energy dissipation.…”
Section: Introductionmentioning
confidence: 99%
“…Initial attempts to model CE events were limited to 1-dimensional studies, such as those reported by Taam et al (1978), Meyer & Meyer-Hofmeister (1979), and Delgado (1980). Using such 1-d studies, three phases have been identified in the evolution of CE simulations (Podsiadlowski 2001;Ivanova 2002): first the loss of co-rotation phase, in which the initial embedding of the binary within the envelope occurs. This phase may occur over a long time-scale (depending on the nature of the onset of CE evolution), with the expected initial co-rotation of the system leading to low rates of energy dissipation.…”
Section: Introductionmentioning
confidence: 99%
“…Several estimates exist for the duration of the CE phase. Podsiadlowski (2001), using a stellar evolution code, predicts that a CE phase may last 100 to 1000 yr. CE 3D hydrodynamic simulations of the dynamical in-fall phase (not including ejection) by Ricker & Taam (2012) estimate it to be longer than about 50 d. Passy et al (2012b) find that most of the in-spiral happens within 200 to 300 d, and Ivanova & Nandez (2016) find this to be a few hundred days. The lack of conclusive observational evidence leaves the CE duration unconstrained and motivates the search for observable signatures of CE evolution which could serve as diagnostic of the instabilities of the spiral-in and the history of the mass loss associated with CE evolution.…”
Section: Mass Loss During Common Envelope Evolutionmentioning
confidence: 99%
“…Recombination energy is a "potential" energy in the sense that it is not readily available to drive an envelope expansion at the start of the CE event, but, after the recombination is triggered, it can be useful at the late stages of a CE event. Recombination energy can remove all the remaining bound parts of the envelope if the envelope material starts to recombine after it expands beyond the "recombination" radius (for the definition, see [21]). The discussion on whether the recombination energy can be used for driving the expansion of a CE, or it would be lost as radiation remains active.…”
Section: The Stages Of a Ce Event And The Associated Mass Outflowsmentioning
confidence: 99%
“…The velocity of the ejected material is not constant across the ejecta-see the typical direction-averaged profile in Figure 1. Ivanova and Nandez [21] identified four kinds of matter ejection processes during a CE event. First is an "initial ejection", before the plunge (for exact definitions of various stages, see [21]).…”
Section: The Stages Of a Ce Event And The Associated Mass Outflowsmentioning
confidence: 99%